IMPLEMENTATION OF COGNITIVE BEHAVIORAL PLAY GUIDANCE BASED ON "ANDAI-ANDAI " WITH ISLAMIC VALUES TO DEVELOP RESILIENCE IN PRIMARY SCHOOL - Syska Purnama Sari; Juntika Nurihsan; Yusi Riksa Yustiana; Ipah Saripah (Psikis : Jurnal Psikologi Islami, 2024)
The study of resilience is a study of how individuals who live with high risk adapt and thrive. Resilience is closely related to risk, because the higher the risk faced by individuals, the higher the needs for resilience. Efforts to develop resilience need to be carried out since elementary school, with the role of class teachers who integrate Guidance and Counseling (BK) services into the learning process. The purpose of the study was to determine the implementation of a cognitive-behavioral play guidance model based on “andai-andai” integrated with Islamic values to develop the resilience of elementary school students. The method used is collaborative action research, involving collaboration between researchers and teachers in the learning process of grade V in PPKN subjects which are adjusted to the Operational Guidelines for BK Implementation (POP BK). The learning process uses the “andai-andai” strategy, which is one of the local wisdoms from South Sumatra in the form of stories told orally. The research was conducted in two cycles: the first cycle was training for classroom teachers, and the second cycle was the implementation of play guidance to students. The stages of play guidance include Introductory, Assessment, Middle Stage, and Summary and Evaluation. The results showed that the integration of Islamic values in the play guidance model provided a strong moral and spiritual foundation for students, as well as preserving local wisdom. This model is proven to be effective in increasing students' resilience through the use of interesting game strategies that are relevant to the characteristics of children